Emissions from the combustion of high-potential slurry fuels; Environmental Science and Pollution Research (ESPR); Vol. 29, iss. 25 - Nyashina G. S. Galina Sergeevna; Dorokhov V. V. Vadim Valerjevich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2022, 2022)
Title screen